1989
DOI: 10.1002/andp.19895010505
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Phase Transition in the System [Ag1−x(Na)x]NO3 by Infrared Spectroscopy

Abstract: A b s t r a c t . A complete infrared study of the mixed crystal system of AgNO, and NaNO, is carried out in the region 400-4000 em-'. The study includes internal fundamental normal vibrations of the NO-, ion in the ordered and disordered phases of AgNO, a t different values of the sodium concentration, the I.R. spectrit, spectral band shape intensities, and frequencies of t h r intrrnal modes as functions of the sodium ion concentration. Special attcntion is paid to bending mode, combination mode, asymmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Figure 1 shows that NaNO 2 crystals ðx ¼ 0Þ have three internal fundamental normal vibrations at n 1 ¼ 1325 cm À1 , n 3 ¼ 1271 cm À1 and n 2 ¼ 825 cm À1 which are in agreement with those values calculated by Fahim [21]. The bending mode n 2 , which appears in the IR spectra as a sharp peak in pure NaNO 2 , remains a strong sharp peak as NO À 3 concentration is increased, and agrees with the bending mode of NaNO 3 , compare El-Kabbany et al [22]. The relative intensity of this mode was also increased due to increasing of concentration of NO À 3 ions as shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…Figure 1 shows that NaNO 2 crystals ðx ¼ 0Þ have three internal fundamental normal vibrations at n 1 ¼ 1325 cm À1 , n 3 ¼ 1271 cm À1 and n 2 ¼ 825 cm À1 which are in agreement with those values calculated by Fahim [21]. The bending mode n 2 , which appears in the IR spectra as a sharp peak in pure NaNO 2 , remains a strong sharp peak as NO À 3 concentration is increased, and agrees with the bending mode of NaNO 3 , compare El-Kabbany et al [22]. The relative intensity of this mode was also increased due to increasing of concentration of NO À 3 ions as shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…It is clearly observed that the bands at about 716 cm −1 , 1050 cm −1 and 1358 cm −1 at 20 °C in the solid state of solar salt and TMS series of molten salts were attributed to the vibrations of NO3 − in KNO3.Furthermore, 727 cm −1 , 1070 cm −1 and 1386 cm −1 corresponded to NO3 − in NaNO3. Compared with 20 °C, at 300 °C, the characteristic peaks of NO3 − of the stretching vibration peaks in KNO3 and NaNO3 were changed into one peak at about 730 cm −1 and 1050 cm −1 because of the inhomogeneity and randomness of the ion cluster microstructure with increasing temperature [50], while weaker peak shapes at about 130-1440 cm −1 were not observed. This also illustrated that the arrangement of the cations around NO3 − was very uniform when the two systems were in a solid state [51,52].…”
Section: Raman Spectramentioning
confidence: 87%
“…As the average distance between the cations increases, any intercationic interactions must become progressively weaker and any correlations among the interactions of the cations with the structure must vanish. A simplified model is proposed below for the energy barrier of rotation of the NO 3 group in the mixed crystal system (AgxK1_x)NO 3, as shown in Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…This is a calcite-like structure, but is characterized by disorder of the anions around their three-fold axis. In a previous work [3], we studied the order -disorder phase transition of AgNO 3 by means of IR spectroscopy (400-4000 cm -~) over a wide range of temperature (30-195~ KNOa undergoes a first-order phase transition from the ordered phase II (symmetry Da26-Pma) to the disordered phase I (symmetry D~-R3c) at 135~ [4] ( Fig. la).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation